Strength improvement of adhesively-bonded scarf repairs in aluminium structures with external reinforcements - Moreira, R.D.F. (2016)
Adhesively bonded techniques are an attractive option to repair aluminium structures, compared to more traditional methods. Actually, as a result of the improvement in the mechanical characteristics of adhesives, adhesive bonding has progressively replaced the traditional joining methods. There are several bonded repair configurations, as single-strap, double-strap and scarf. Compared with strap repairs, scarf repairs have the advantages of a higher efficiency and the absence of aerodynamic disturbance. The higher efficiency is caused by the elimination of the significant joint eccentricities of strap repairs. Moreover, stress distributions along the bond length are more uniform, due to tapering of the scarf edges. The main disadvantages of this technique are the difficult machining of the surfaces, associated costs and requirement of specialised labour. This work reports on an experimental and numerical study of the tensile behaviour of two-dimensional (2D) scarf repairs of aluminium structures bonded with the ductile epoxy adhesive Araldite® 2015. The numerical analysis, by Finite Elements (FE), was performed in Abaqus® and used cohesive zone models (CZM) for the simulation of damage onset and growth in the adhesive layer, thus enabling the strength prediction of the repairs. A parametric study was performed on the scarf angle (α) and different configurations of external reinforcement (applied on one or two sides of the repair, and also different reinforcement lengths). The obtained results allowed the establishment of design guidelines for repairing, showing that the use of external reinforcements enables increasing α for equal strength recovery, which makes the repair procedure easier. The numerical technique was accurate in predicting the repairs’ strength, enabling its use for design and optimisation purposes.